A national audit of colonic interposition for esophageal replacement. Issue 5 (29th March 2017) - Fisher, R. A.; Griffiths, E. A.; Evison, F.; Mason, R. C.; Zylstra, J.; Davies, A. R.; Alderson, D.; Gossage, J. A.
SUMMARY: Esophageal replacement by colonic interposition is an uncommon procedure. This study sought to identify the frequency of this operation in England, identify techniques and associated problems, and also assess health-related quality of life (HR QOL) from the two largest centers performing this procedure. Hospital Episode Statistics were used to identify patients and centers undertaking colon interposition between March 2001 and March 2015. An online survey of UK consultants discussed methods and experience. HR QOL was assessed using the Short Form 36(SF-36v2) with additional gastrointestinal questions. Hospital Episode Statistics identified 328 interpositions (22 in pediatric hospitals). The two highest volume units did 42 and 45 operations, respectively. Thirty-four surgeons (79% response rate) replied to the survey. Fifty-two percent preferred to use the left colon with 81% preferring a substernal placement. The HR QOL survey was performed on 24 patients with a median of 3 years after surgery (ranging from 9 months to 10 years) from the two largest centers and a 56% response rate. Five patients had physical QOL scores above population average and 10 had mental scores above population average. All patients had early satiety, 20 described dysphagia, and 18 regularly took antireflux medication. There was an estimated mean loss of 13.1% body weight (10.6 kg) postoperatively and three patients still relied on a feeding tube for nutrition after an average of 3 years. Colon interposition results in an acceptable long-term QOL. Few centers regularly perform this operation, and centralizing to high-volume centers may lead to better outcomes.